A detailed study of the H.E.S.S. data from the Galactic Center region - Nekrassov, Daniil (2010)
The High Energy Stereoscopic System, H.E.S.S., is an array of four imaging atmospheric Cherenkov telescopes, located in the Khomas highlands of Namibia, designed for the exploration of very high-energy (E > 100 GeV) gamma-ray emission in the universe, arising in non-thermal processes. Its location in the southern hemisphere renders sensitive observations of a large region of the Galactic Plane possible. In particular, a deep exposure of the Galactic Center region allows detailed studies of the observed em ission, helping to identify the sources of the radiation and the physics processes at play. In this thesis, new methods are developed to study both the morphological and spectral properties of diffuse very high-energy gamma-ray emission from the Galactic Center region. Assuming that the radiation originates from hadronic interactions of diffusing cosmic rays with the ambient matter, this study helps to constrain the parameter space of cosmic-ray diffusion in the Galactic Center region. The second part of this work introduces new methods to search for signals of Dark Matter annihilations, putting upper-limits on the production of spectral line features in the H.E.S.S. Galactic Center data. Finally, an upper-limit on the total annihilation cross-section of Dark Matter particles is derived.